Synthesis and Application of SiO2/NbOx Composites for Environmental Remediation by Adsorption - Carla de Albuquerque Dias; Armindo Santos; Dayane Izabelita Santos Lacerda; Harlley Sander Silva Torres; Jefferson Arlen Freitas; Sérgio Carneiro Reis; Querem Hapuque Felix Rebelo (Materials Research)
In this study, a novel SiO2/NbOx composite was synthesized through high-energy mechanical milling followed by thermal treatment, aiming to explore its effectiveness as an adsorbent for environmental remediation. The composite was thoroughly characterized using techniques such as X-ray diffraction (XRD), X-ray fluorescence (XRF), nitrogen adsorption-desorption isotherms, thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). The XRD analysis confirmed the amorphous nature of the SiO2/NbOx composite, with a significant presence of Nb (81.1%) compared to Si (15.8%), as indicated by XRF analysis. Adsorption studies were conducted using methylene blue (MB) dye in aqueous solution, evaluating the adsorption capacity and kinetics under controlled conditions. The composite demonstrated a rapid adsorption capacity, reaching 39.32 mg g−1 in a short time, following a pseudo-second-order kinetic model. The Langmuir isotherm model fitted the adsorption data, indicating a maximum capacity of 16.7 mg g−1. The findings highlight the potential of SiO2/NbOx as an efficient adsorbent for dye removal, contributing to environmentally friendly solutions for wastewater treatment.